2021
DOI: 10.3390/app11093786
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exposure on the Microbial Consortiums on Historical Rural Granite Buildings

Abstract: Local granite has been used throughout history in Galicia (NW Spain), forming the basis of much of the region’s architecture. Like any other rock, granite provides an ecological niche for a multitude of organisms that form biofilms that can affect the physical integrity of the stone. In this study, for the first time, characterization of the microbial consortium forming biofilms that developed on historical rural granite buildings is carried out using a combination of culture-dependent and next generation sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
3
5
0
Order By: Relevance
“…This analysis is in accordance with biofilms' composition where the presence of microorganisms from the Trentepohlia species in Surface b is associated with a large production of carotenoids, especially β-carotene (followed by zeaxanthin, neoxanthin, lutein, ascorbic acid and α-tocopherol), which protects them from energetic UVa and UVb solar radiation. These photosynthetic pigments give these terrestrial algae a typical yellow-orange and red coloration, in accordance with what can be observed by the naked eye [39,53,54].…”
Section: Gloeocapsa Punctatasupporting
confidence: 87%
See 1 more Smart Citation
“…This analysis is in accordance with biofilms' composition where the presence of microorganisms from the Trentepohlia species in Surface b is associated with a large production of carotenoids, especially β-carotene (followed by zeaxanthin, neoxanthin, lutein, ascorbic acid and α-tocopherol), which protects them from energetic UVa and UVb solar radiation. These photosynthetic pigments give these terrestrial algae a typical yellow-orange and red coloration, in accordance with what can be observed by the naked eye [39,53,54].…”
Section: Gloeocapsa Punctatasupporting
confidence: 87%
“…As travertine was chosen in our previous study [28] as a representative artistic and historical material for the city of Rome [37], for the same reason, granite has been selected because its wide diffusion in Santiago de Compostela, where this study was carried out and where the most relevant historical and artistic sites are typically made of this lithotype [38,39]. What is reported above fits with our long-term goal, which foresees the ideation of a protocol for the in situ treatment of a wide range of lithotypes, taking into account the intrinsic characteristics of the treated stone (porosity, roughness, scratch resistance, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional techniques and the conditions in which the heritage stones have been extracted from the historical quarry, carved and placed in the monument are key to understanding its deterioration and conservation. The challenges of heritage stone research in the 21st century are: climate change mitigation, monitoring, remote sensing [238][239][240][241], adaptation [242], restoring after conflicts, disasters, or pandemics, the achievement of sustainable development goals [243][244][245][246][247][248][249], and most importantly, the preservation of a legacy for the future.…”
Section: Recent Workmentioning
confidence: 99%
“…For instance, Nattaphon Suphaphimol found that the fungal diversity was different between the two temples with distinct visitor flow rates in Chiang Mai, Thailand, and microorganisms like Aspergillus , Malassezia , and Toxicocladosporium which belong to human skin were found on the one with higher visitor flow rate, the Buak Krok Luang temple 16 . However, at the same time, Elsa Fuentes compared the Granite Buildings located in rural and urban areas and found that the diversity of fungi in the two places was extremely similar 17 . Tianxiao Li et al 4 studied the microbiome on the steles of Lingyan Temple and determined that changes in the air microbiome due to natural rainfall, plant respiration, and numerous visitors also affected the composition of the stele surface microbiota, but the contribution of human traffic to changes in the microbiome was unclear.…”
Section: Introductionmentioning
confidence: 99%